Analisis Faktor Kejadian Anemia Gizi Pada Remaja Putri di SMP Sriwijaya Palembang - Sartika, Tri; Handayani, Tri Restu (REAL in Nursing Journal, 2023)
Background: The incidence of anemia in adolescents is still very high, namely above 20%, 26.8% in children aged 5 to 14 years, 32% in children aged 15 to 24 years. This high incidence of anemia is closely related to compliance in consuming Blood Supplement Tablets (TTD). The aim of the research is to determine the analysis of factors in the incidence of nutritional anemia in young women. Methods: This research is a quantitative research with a cross sectional research design. The research population was Sriwijaya Middle School students in Palembang, South Sumatra, with a sampling technique, namely a total population of 25 respondents. The measuring method used was an interview with the measuring instrument used was an open questionnaire about anemia in adolescents. Data analysis was carried out using the univariate analysis method to determine the frequency distribution of the variables studied, and the relationship between variables was carried out using bivariate analysis using the chi-square method. Results: The results of the research show that there is a significant relationship between the variables Knowledge p value 0.005, Nutrition p value 0.005 and maternal education level p value 0.049 with the incidence of nutritional anemia in young women at Sriwijaya Middle School in 2023. In the variables Attitude and menstrual patterns it is known that the p value is >0.05 which This means that there is no significant relationship with the incidence of anemia in adolescent girls. Conclusion: Based on the research results, it can be concluded that there is still low exposure to information regarding the risk of anemia, especially among adolescent girls, so there is a need for active health promotion regarding the risk of stunting in adolescent girls, especially the incidence of nutritional anemia.